(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article is devoted to the study of the factors of formation of teachers’ readiness for successful innovation activity (GOTIN) and identification of barriers that hinder its development. The article summarizes the definition of GOTIN in the scientific literature, considers its key components (motivational, cognitive, activity, reflexive, and creative), and identifies the main criteria that characterize the level of GOTIN. The central phenomenon from which GOTHINN develops is openness to the new. It ensures the perception of innovations and the teacher’s ability to be creative. However, its formation can be complicated by a number of barriers: cognitive (e.g., stagnation of intelligence), social (lack of positive examples among colleagues), organizational (excessive documentation, overload), methodological (lack of quality resources), material (low salary) and psychological (anxiety, fear of change, low self-esteem). It is determined that the key factor in overcoming these barriers is pedagogical motivation, which can be both selfish (self-development, intellectual curiosity) and altruistic (desire to improve the educational process) in nature. Methods of identifying barriers in the pedagogical environment, in particular, “independent survey” are proposed. Strategies for overcoming them are outlined, including motivational support, reducing bureaucratic burden, training programs for managers, and psychological assistance to teachers. The article concludes that GOTS is an important component of a teacher’s professional activity, and its formation depends on a systematic approach that includes personal, organizational, and socio-cultural aspects. Further research could be aimed at developing effective educational strategies to stimulate teachers’ innovative activity and create conditions for their professional growth.